Qili Qiangxin capsules for chronic heart failure: A GRADE-assessed clinical evidence and preclinical mechanism - Xiaoxiao Xing; Jianbo Guo; Jianbo Guo; Juefei Mo; Huashan Li; Hui Zhang; Baoyi Shao; Yifan Wang; Haidi Li; Jianan Wang; Jianan Wang; Cheuk Lung Leung; et al. (Frontiers in Cardiovascular Medicine, 2023)
IntroductionChronic heart failure (CHF) has become an increasing concern with the aging of the population. This study aims to evaluate the effectiveness and safety of Qili Qiangxin capsules (QLQX) for CHF.MethodsA systematic review and meta-analysis on clinical studies was conducted. The mechanisms of preclinical studies were summarized.ResultsWe searched six electronic databases by 20 July 2022, and finally, 7 preclinical experiments (PEs) and 24 randomized controlled trials were included. The risk of bias was accessed by the SYRCLE and RoB 2.0 tool, respectively. PEs indicated that QLQX suppresses myocardial apoptosis, inhibits renin-angiotensin-aldosterone system activation, improves water retention, and enhances cardiocyte remodeling. In clinical studies, compared with routine treatment, QLQX could improve the indicators: clinical efficacy rate (RR = 1.16, 95% CI [1.12, 1.22], GRADE: moderate), left ventricular end-diastolic dimension (SMD = −1.04, 95% CI [−1.39, −0.70], GRADE: low), left ventricular ejection fraction (SMD = 1.20, 95% CI [0.97, 1.43], GRADE: moderate), 6-minute walk distance (SMD = 1.55, 95% CI [0.89, 2.21], GRADE: low), brain natriuretic peptide (SMD = −0.78, 95% CI [−1.06, −0.51], GRADE: low), N-terminal pro-brain natriuretic peptide (SMD = −2.15, 95% CI [−3.60, −0.71], GRADE: low), and adverse events (RR = 0.46, 95% CI [0.25, 0.87], GRADE: low).DiscussionIn summary, QLQX exerts a potential mechanism of utility on myocardial apoptosis and cardiac function and has noteworthy clinical adjuvant efficacy and safety in patients with CHF.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/.